The Coaching Maps – geneza innowacyjnego narzędzia - Robert Geisler (Studia i Materiały)
The aim of the article is analysis of the innovative product – The Coachng Maps – its origin and implementation. The tool was created as result of the research in economic sociology and business psychology. It is product relevant to contemporary social and economic context in 21 century as result of scientific research and practice regarding knowledge management, training and coaching. The analysis of case study concern origin of innovation and process building innovation as interactive social process. Implementation of the innovation will be the second part of the analysis, especially in the context of entrepreneurial model in 21 century.